1999
DOI: 10.1038/sj.bjc.6690070
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow angiogenesis and mast cell density increase simultaneously with progression of human multiple myeloma

Abstract: Immunohistochemical, cytochemical and ultrastructural data showing vivid angiogenesis and numerous mast cells (MCs) in the bone marrow of 24 patients with active multiple myeloma (MM) compared with 34 patients with non-active MM and 22 patients with monoclonal gammopathy of undetermined significance (MGUS) led us to hypothesize that angiogenesis parallels progression of MM, and that MCs participate in its induction via angiogenic factors in their secretory granules. © 1999 Cancer Research Campaign

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
141
0
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 234 publications
(149 citation statements)
references
References 31 publications
4
141
0
4
Order By: Relevance
“…The discrepancies in previous studies (Veiga et al, 1998;Hyjek et al, 1999;Ribatti et al, 1999;Vacca et al, 1999b;Arias and Soares, 2000;Ridell and Norrby, 2001) concerning MVD values in reactive lymphoid tissues and lymphomas were the primary issue for this investigation. Our data confirm that both in reactive lymph nodes and in lymph nodes with follicular lymphomas, the MVD is higher in the paracortex than in the follicles and that there is no difference in MVD between reactive germinal centres and neoplastic follicles.…”
Section: Discussionmentioning
confidence: 82%
“…The discrepancies in previous studies (Veiga et al, 1998;Hyjek et al, 1999;Ribatti et al, 1999;Vacca et al, 1999b;Arias and Soares, 2000;Ridell and Norrby, 2001) concerning MVD values in reactive lymphoid tissues and lymphomas were the primary issue for this investigation. Our data confirm that both in reactive lymph nodes and in lymph nodes with follicular lymphomas, the MVD is higher in the paracortex than in the follicles and that there is no difference in MVD between reactive germinal centres and neoplastic follicles.…”
Section: Discussionmentioning
confidence: 82%
“…8 MC density is highly correlated with the extent of both normal and pathological angiogenesis, such as that in chronic inflammatory diseases and tumors. 9 We have demonstrated that in multiple myeloma and B cell non-Hodgkin's lymphoma there is a striking association between MC and microvessel counts and that both increase in function of tumor progression, as defined by its increasing malignancies grades, 10,11 while in both benign lymphadenopathies and in B cell non-Hodgkin's lymphoma angiogenesis is highly correlated with the total and MC tryptase-positive counts. 12 Tryptase contained in MC secretory granules is angiogenic both in vitro and in vivo experimental models, and specific tryptase inhibitors suppress this activity.…”
Section: Introductionmentioning
confidence: 95%
“…[1][2][3] These data, together with the known anti-angiogenic properties of thalidomide, 4 provided the rationale for the use of thalidomide in the treatment of patients with MM. 5 Remarkably, thalidomide induced clinical responses in 32% of MM patients whose disease was refractory to conventional and even to high-dose chemotherapy, 5 suggesting that thalidomide can overcome in vivo drug resistance.…”
Section: Introductionmentioning
confidence: 99%